The Past, Present and Future of International Health Evaluation Association (IHEA) - Hinohara, Shigeaki (Methods of Information in Medicine, 2002)
In this paper I mention the 19-year history of International Health Evaluation Association (IHEA) which was started in Washington D.C. by the great effort of Dr. G. Gilbert in Hawaii. In 1973 three regions were organized in this Association: 1) U.S.A., 2) Europe and 3) Pan-Pacific including Asia.I also mention the history of periodical health checkups in U.K., U.S.A. and Japan. In Japan it started in 1954, however, after adapting the system of Automated Multiphase Health Testing designed by the Kaiser Foundation of Auckland, Calif., in 1973, Japanese people paid much attention to this health screening system and the number of hospitals and clinics for health screening has increased tremendously and the number of examinees amounted to 2,875,449 in 2001.Finally, I conclude that IHEA should create a multi-disciplinary system to sustain a lifestyle with a high level of Quality of Life (QOL) for the people who really want to live fruitful lives by the successive health education.
Keywords: Periodic health check-ups; multiphase health testing; health promotion